Angst, Glaube und Liebe in M. Night Shyamalans „The Village“ - Pinsch, Jan Christian (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik)

Religiöse Feindbilder. Bausteine für die Sekundarstufe II - Pinsch, Jan Christian; Arnhold, Oliver; Lerke, Stephanie

Food - Media - Senses

Lessons Learned from the Introduction of Systems Engineering - Wilke, Daria; Grothe, Robin; Bretz, Lukas; Anacker, Harald; Dumitrescu, Roman (Systems)
The introduction of Systems Engineering is an approach for dealing with the increasing complexity of products and their associated product development. Several introduction strategies are available in the literature; nevertheless, the introduction of Systems Engineering into practice still poses a great challenge to companies. Many companies have already gained experience in the introduction of Systems Engineering. Therefore, as part of the SE4OWL research project, the need to conduct a study including expert interviews and to collect the experiences of experts was identified. A total of 78 hypotheses were identified from 13 expert interviews concerning the lessons learned. Using exclusion criteria, 52 hypotheses were validated in a subsequent quantitative survey with 112 participants. Of these 52 hypotheses, 40 could be confirmed based on the survey results. Only four hypotheses were rejected, and eight could neither be confirmed nor rejected. Through this research, guidance is provided to companies to leverage best practices for the introduction of their own Systems Engineering and to avoid the poor practices of other companies.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Soziotechnische Gestaltung einer intelligenten Personaleinsatzplanung - Gabriel, Stefan; Bentler, Dominik; Bansmann, Michael; Andrew Latos, Benedikt; Kühn, Arno; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract In diesem Beitrag wird die soziotechnische Gestaltung einer Intelligenten Personaleinsatzplanung beim Unternehmen Miele & Cie. KG im Rahmen des Leuchtturmprojekts „InTime“ im Kompetenzzentrum Arbeitswelt.Plus beschrieben. Hierzu werden die Durchführung und Auswertung einer Interviewreihe sowie das daraus erarbeitete Soll-Konzept vorgestellt.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Soziotechnisches Risikomanagement als Erfolgsfaktor für die Digitale Transformation - Menzefricke, Jörn Steffen; Gabriel, Stefan; Gundlach, Thomas; Hobscheidt, Daniela; Kürpick, Christian; Schnasse, Felix; Scholtysik, Michel; Seif, Heiko; Koldewey, Christian; Dumitrescu, Roman (Schwerpunkt Business Model Innovation)

Partizipatives Gestaltungsvorgehen bei der Einführung künstlicher Intelligenz in produzierenden Unternehmen - Bentler, Dominik; Gabriel, Stefan; Latos, Benedikt A.; Dietrich, Oliver; Dumitrescu, Roman; Maier, Günter W. (GfA-Frühjahrskongress 2023)

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Design of individual simulation games in manufacturing companies for game-based learning - Machon, Fabian; Gabriel, Stefan; Latos, Benedikt; Holtkötter, Christoph; Lütkehoff, Ben; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Process Mining Data Canvas: A method to identify data and process knowledge for data collection and preparation in process mining projects - Brock, Jonathan; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Targeted-oriented selection of engineering methods - Wilke, Daria; Schierbaum, Anja; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Which Types of Workers Are Adversely Affected by Digital Transformation? Insights from the Task-Based Approach - Hellweg, Talea; Schneider, Martin (The Digital Twin of Humans. An Interdisciplinary Concept of Digital Working Environments in Industry 4.0)

Digital Twins in Flexible Online Work: Crowdworkers on German-Language Platforms - Hemsen, Paul; Reimann, Mareike; Schneider, Martin (The Digital Twin of Humans. An Interdisciplinary Concept of Digital Working Environments in Industry 4.0)

On the Membership and Correctness Problem for State Serializability and Value Opacity - König, Jürgen

XCS for Self-awareness in Autonomous Computing Systems - Hansmeier, Tim

Who Will Own Our Global Digital Twin: The Power of Genetic and Biographic Information to Shape Our Lives - Pilz, Sarah; Hellweg, Talea; Harteis, Christian; Rückert, Ulrich; Schneider, Martin (The Digital Twin of Humans. An Interdisciplinary Concept of Digital Working Environments in Industry 4.0)

Improved Hardness Results for the Guided Local Hamiltonian Problem - Gharibian, Sevag; Hayakawa, Ryu; Gall, François Le; Morimae, Tomoyuki (Proceedings of the 50th EATCS International Colloquium on Automata, Languages and Programming (ICALP))
Estimating the ground state energy of a local Hamiltonian is a central problem in quantum chemistry. In order to further investigate its complexity and the potential of quantum algorithms for quantum chemistry, Gharibian and Le Gall (STOC 2022) recently introduced the guided local Hamiltonian problem (GLH), which is a variant of the local Hamiltonian problem where an approximation of a ground state is given as an additional input. Gharibian and Le Gall showed quantum advantage (more precisely, BQP-completeness) for GLH with $6$-local Hamiltonians when the guiding vector has overlap (inverse-polynomially) close to 1/2 with a ground state. In this paper, we optimally improve both the locality and the overlap parameters: we show that this quantum advantage (BQP-completeness) persists even with 2-local Hamiltonians, and even when the guiding vector has overlap (inverse-polynomially) close to 1 with a ground state. Moreover, we show that the quantum advantage also holds for 2-local physically motivated Hamiltonians on a 2D square lattice. This makes a further step towards establishing practical quantum advantage in quantum chemistry.

Ungeliebte Tiere in der Stadt - Tenberge, Claudia (Grundschule Sachunterricht)

A PRACTICAL HANDBOOK ON EFFECTIVE DEVELOPMENT AND IMPLEMENTATION OF STEAM TEACHING AT SCHOOL

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering